1992
DOI: 10.1093/carcin/13.4.579
|View full text |Cite
|
Sign up to set email alerts
|

Composition and turnover of phospholipids and neutral lipids in human breast cancer and reference tissues

Abstract: The phospholipid (PL) content was 4-fold higher while the triacylglycerol (TG) content tended to be 65% lower in human breast cancer tissues as compared with non-cancerous reference parts from excised breast tissues. The variation in TG content among breast tissues was very large while that of PL was relatively small. The fatty acid compositions of PL were significantly different between the cancer and reference tissues; the proportions of octadecenoate (18:1), docosahexaenoate (22:6n-3), the total n-3 fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 0 publications
6
44
0
Order By: Relevance
“…Previous studies indicate that the phospholipid content is 4-fold higher and the triacylglycerol content is 65% lower in cancer compared with noncancerous parts of the breast tissue (40). Moreover, the fatty acid composition of the cancer tissue phospholipids was highly enriched in unsaturated FFAs compared with noncancerous tissue, whereas triacylglycerol revealed no significant difference between cancer and normal tissue (40). Consistent with these observations, cis unsaturated FFAs are the predominant FFAs released from breast cancer tissue (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies indicate that the phospholipid content is 4-fold higher and the triacylglycerol content is 65% lower in cancer compared with noncancerous parts of the breast tissue (40). Moreover, the fatty acid composition of the cancer tissue phospholipids was highly enriched in unsaturated FFAs compared with noncancerous tissue, whereas triacylglycerol revealed no significant difference between cancer and normal tissue (40). Consistent with these observations, cis unsaturated FFAs are the predominant FFAs released from breast cancer tissue (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Microscopic examination of dispersions of cells from selected breast tumor samples did not reveal significant amounts of intracellular lipid droplets (data not shown). Previous studies indicate that the phospholipid content is 4-fold higher and the triacylglycerol content is 65% lower in cancer compared with noncancerous parts of the breast tissue (40). Moreover, the fatty acid composition of the cancer tissue phospholipids was highly enriched in unsaturated FFAs compared with noncancerous tissue, whereas triacylglycerol revealed no significant difference between cancer and normal tissue (40).…”
Section: Discussionmentioning
confidence: 87%
“…Among the highly significant peaks identified were several fatty acids (FA), phosphatidylethanolamines (PE), phosphatidylcholines (PC) and phosphatidylinositols (PI). Fold changes between 2 and 14 were observed (mean fold change ¼ 5), which is close to fold changes reported in the literature (30,31). Only a small number of peaks with medium significance for tissue separation were found in greater abundance in the morphologically normal glandular tissue.…”
Section: Tissue-specific Metabolomic Profilingsupporting
confidence: 87%
“…The most intense peaks, with a P value < 2 Â 10 À5 , are summarized in Table 3. Very high fold changes (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) were found for signals associated with lactate and calcidiol. Lactate was found as a dimer and in form of several sodium chloride clusters (MþNa 4 Cl 4 , MþNa 3 Cl 3 , MþNa 2 Cl 2 ).…”
Section: Tissue-specific Metabolomic Profilingmentioning
confidence: 99%
“…The most widely recognized role of lipids is to form the lipid bilayer of cellular and organelle membranes [8]. It has been reported that alterations in the glycerophospholipid composition of tissues occur in several diseases, including cancer [9] and Alzheimer's disease [10]. Particular glycerophospholipids and their enzymatic products have been identified in malignant transformations in tissue [11,12].…”
mentioning
confidence: 99%